2005
DOI: 10.1177/154405910508401121
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength of Mineralized/Demineralized Human Normal and Carious Dentin

Abstract: The bond strengths of resins to caries-affected dentin are low. This could be due to weakened organic matrix. The purpose of this work was to determine if the ultimate tensile strength (UTS) of excavated carious dentin is weaker than that of normal dentin. Soft caries was excavated from extracted human molars, and the tooth was vertically sectioned into slabs. Each slab was trimmed to an hourglass shape, parallel or perpendicular to the tubule direction. Half of the specimens were mineralized, while the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 15 publications
2
30
0
6
Order By: Relevance
“…It is therefore not surprising to find un-infiltrated, exposed collagen below the hybrid layer in composite restorations. The exposed collagen becomes a weak link in the adhesive bonding of composite restorations [47]. …”
Section: Resultsmentioning
confidence: 99%
“…It is therefore not surprising to find un-infiltrated, exposed collagen below the hybrid layer in composite restorations. The exposed collagen becomes a weak link in the adhesive bonding of composite restorations [47]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, ultimate tensile strength (UTS) of caries-affected dentin is also lower than that of normal dentin, and there is a positive correlation in caries-affected dentin between the UTS and the Knoop hardness number [6]. On the other hand, Nishitani et al [32] reported that the matrix of demineralized cariesaffected dentin was as strong as that of normal demineralized dentin. These results would indicate that lower UTS and hardness of caries-affected dentin are due to loss of mineral in intertubular dentin.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…While all dentin matrices display a similar structural plan, there are distinct functional attributes for each type (Zaytsev et al, 2012). Considering the loss of tooth structure in extensive caries and the compromised APd resulting from the carious process (Nishitani et al, 2005), there is a requirement for Rd to provide an appropriate deformable and resilient foundation to resist tooth fracture under high stress. This modification manifests as a lower elastic modulus reported for Rd compared to APd (Senawongse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%